The multimodal transcriptional response of denervated skeletal muscle involves regulation of Gramd1 genes impacting muscle size - Cristofer Calvo; Casey O. Swoboda; Fabian Montecino-Morales; Siddhant Nagar; Michael J. Petrany; Chengyi Sun; Hima Bindu Durumutla; Mattia Quattrocelli; Douglas P. Millay (Proceedings of the National Academy of Sciences, 2025)
The development and maintenance of the neuromuscular junction (NMJ) requires reciprocal signals between the nerve terminals and multinucleated skeletal muscle fibers (myofibers). This interaction drives highly specialized transcription in the subsynaptic or NMJ myonuclei within mature myofibers leading to clustering of acetylcholine receptors (AChRs). Here, we utilized single-nucleus RNA sequencing (snRNA-seq) to delineate the transcriptional response of myonuclei to denervation. Through snRNA-seq on skeletal muscle from two independent mouse models of denervation, sciatic nerve transection and amyotrophic lateral sclerosis, we identify a multimodal transcriptional response of NMJ-enriched genes and an alteration in cholesterol homeostasis in myofibers. Gramd1 , a family of genes involved in nonvesicular cholesterol transport, are enriched at the NMJ in innervated muscle and upregulated in both models of denervation by the NMJ and extrasynaptic myonuclei. In vivo gain and loss of function studies indicate that Gramd1 genes regulate myofiber sizes. Mechanistically, we did not detect obvious changes in AChR clustering due to Gramd1 knockdown but revealed a role in autophagy after denervation. We uncovered a dynamic transcriptional response of myonuclei to denervation and highlight a critical role for Gramd1 to maintain myofiber sizes.